WORKING CAPITAL AS AN ENTERPRISE VALUE ASSESSMENT TOOL - Bruna, Inta; Millere, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The valuation of an entity in off-exchange transactions involves the use of different techniques. Nevertheless, none of them guarantees the most accurate result. Therefore, it is very difficult to choose one evaluation method. Both investors, corporate managers, financial professionals, portfolio managers, and securities analysts should have a basic understanding of the process of evaluating companies. To that end, professionals recommend evaluating a company’s financial reports to detect its financial position and solvency. According to the methods of financial analysis, working capital is one of the solvency ratios, which describes the value of resources that remain after the company’s current liabilities have been bared. The research study is aimed at determining the impact of changes in working capital on the valuation of a company. In order to achieve the aim and confirm or deny the hypothesis, the methodological basis for the research study was developed, necessary information was collected, calculations were performed using data from companies listed on Nasdaq OMX Riga, and the obtained results were analysed. Literature review and economic and statistical analysis, including the SPSS method for assessing the effects of working capital and stock price, were used in the research.